2018
DOI: 10.2214/ajr.17.18708
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers and Imaging of Breast Cancer

Abstract: Clinical breast care and breast cancer-related research rely on imaging biomarkers for decision support. In the era of precision medicine and big data, the practice of radiology is likely to change. A closer integration of breast imaging with related biomedical fields and the creation of large integrated and shareable databases of clinical, molecular, and imaging biomarkers should allow the field to continue guiding breast cancer care and research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 75 publications
1
43
0
3
Order By: Relevance
“…Quantitative imaging data can potentially be used in a variety of ways. 1 On an individual patient basis, quantitative spine imaging data can be used in these arenas:…”
Section: Uses Of Quantitative Spine Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative imaging data can potentially be used in a variety of ways. 1 On an individual patient basis, quantitative spine imaging data can be used in these arenas:…”
Section: Uses Of Quantitative Spine Imagingmentioning
confidence: 99%
“…The objective data provided should be precise, reproducible, and clinically relevant. 1 One of the frustrating features currently of quantitative spine imaging is the variability of data reported by different, seemingly rigorously conducted studies. For example, comparing studies reporting cervical cord crosssectional area (CSA), two studies on asymptomatic European and Japanese subjects, respectively, reported values of $ 72 to 79 mm 2 for cervical cord CSA.…”
Section: Data Reliabilitymentioning
confidence: 99%
“…Obviously CAD can be considered part of radiomics, but in contrast to CAD's simplicity and ability for answering only simple clinical questions, radiomic analysis considers more complex computational processes aiding decision support, by utilizing a plethora of quantitative imaging features—potential imaging biomarkers, extracted from digital images [ 26 , 28 ]. Furthermore, the correlation of these large-scale radiological phenotypic characteristics with the rich breast histopathological data available, e.g., the expression statuses of estrogen receptor (ER), progesterone receptor (PR), human epidermal growth factor 2 receptor (HER2), and triple negative (lack of expression of ER, PR, and HER2), facilitates their strong association with molecular subtypes, which eventually results in the generation of pathology prognostic and predictive models [ 4 , 26 , 27 , 29 ].…”
Section: Radiomics and Decision Support In Breast Mrimentioning
confidence: 99%
“…After tumor delineation, radiomic features are extracted from the information contained in the segmented ROIs that can be used to qualitatively assess tumor phenotype, aggressiveness, treatment response, and cancer genetics, and differentiate between benign and malignant tumors [ 5 ]. The further processing and selection between the varieties of radiomic features derived leads to the potential definition of qualitative imaging biomarkers (QIB) that holds prognostic and predictive values for cancer outcome [ 28 ]. Therefore, when found to have significant correlation with tumor's biological properties, these parameters may possibly serve as useful endpoints for the assessment of the severity, degree of change, or status of a cancer lesion, relative to normal [ 22 ].…”
Section: Radiomics Analysis Workflowmentioning
confidence: 99%
See 1 more Smart Citation